PENGUATAN EKONOMI PEREMPUAN ADAT MELALUI TATA KELOLA KEUANGAN DIGITAL DAN STRATEGI PEMASARAN PRODUK UNGGULAN HaL-PA: STRENGTHENING THE ECONOMY OF INDIGENOUS WOMEN THROUGH DIGITAL FINANCIAL GOVERNANCE AND MARKETING STRATEGIES FOR HAL-PA'S FEATURED PRODUCTS - Fitri Handayani; Hermawan Sutanto; Yessica Sardina Purba (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
Indigenous women play a crucial role in supporting the household economy and preserving local wisdom, yet they still face various limitations in financial management, technology, and marketing strategies. This community service program aims to strengthen partners' capacity through digital financial management, training in hygienic packaging in accordance with halal standards, and optimizing digital marketing for HaL-PA's flagship products. Implementation methods include surveys, needs mapping, outreach, interactive training, and ongoing mentoring involving lecturers and students. The program's implementation includes the use of a simple financial recording application, the provision of appropriate technology such as vacuum sealers and labeling machines, and the use of social media for branding and market expansion. Results from this activity indicate increased digital literacy, more hygienic product quality, and enhanced competitiveness through product diversification, trademark management, and halal certification. Recommendations for follow-up include strengthening product innovation and the sustainability of digital marketing strategies.